The Overview of Satisfaction Level of Online Learning System Student During Covid 19 Pandemic - Wijanarko Heru Pramono; Emilia Puspitasari Sugiyanto; Candra Hadi Prasetyo (Proceedings of the International Conference on Nursing and Health Sciences, 2020)
The social restriction during Covid-19 pandemic impact sector particularly education. Education providers were competing to make changes in order to sustain the learning and teaching activity. Every education system basically will determine the quality of learning by measuring the student satisfaction level. These statisfaction levels reflect how good or bad the learning quality in a college. This quantitative study aims to examine the quality of online learning system in the Nrsing program of Widya Husada University, Semarang, Indonesia. This study was conducted on 144 students using quantitative methods with a cross sectional approach. Research analysis using with deskriptif analysis. This study students of the Nursing program were involved in this study and asked to fill the questionnaire as data collection. The results showed that the student satisfaction was mostly expressed in less than 60.4%. This fact was affected by several things including gender, level, domicile, student readiness, network quality, the ability of the lecturer to provide the material and application tools provided.Based on the result of this study it can be conclude that the student satisfaction is low.